If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 2 + -1x + -1 Reorder the terms: -3 + 4x = 2 + -1x + -1 Reorder the terms: -3 + 4x = 2 + -1 + -1x Combine like terms: 2 + -1 = 1 -3 + 4x = 1 + -1x Solving -3 + 4x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 4x + x = 1 + -1x + x Combine like terms: 4x + x = 5x -3 + 5x = 1 + -1x + x Combine like terms: -1x + x = 0 -3 + 5x = 1 + 0 -3 + 5x = 1 Add '3' to each side of the equation. -3 + 3 + 5x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 1 + 3 5x = 1 + 3 Combine like terms: 1 + 3 = 4 5x = 4 Divide each side by '5'. x = 0.8 Simplifying x = 0.8
| x^2-13x=60 | | 4y-5=-29 | | 3(r+2)=1 | | 2(X^2+8X-3)=0 | | In(x)=80 | | w^2-5w+7-35=0 | | -15+j=19 | | 20x+48=33x+9 | | lnx=80 | | (2ab)2a-0.5b=1.2 | | 14=x+169 | | 4/5t+2/5=2/3 | | 12x=4(x+10) | | r-(-10.2)=-7.3 | | 9(n-1)=6(y-3) | | 7y-2=14y+26 | | 5(n+2)=5+10m | | 19-(3m+5)=5+2m-11 | | 6p^2+15p-63=3p+3p^2 | | Y+4=3(-1) | | 8(2x-5)-8x=4-4(x-1) | | -3+4=3 | | -144=2y | | 11(11x-7)=-4 | | -7+4(1+6n)=32 | | ((5)(5))+((5)(5))=((c)(c)) | | 7(u-3)-7=-3(-9u+4)-8u | | (y-30)+2y=90 | | -4(2-7d)=5(5-h) | | 0.5x+-3.5=0.2x-0.5 | | x^2-20=3x-10 | | 180=80+3x |